Reference ranges of fetal aortic and pulmonary valve diameter derived by STIC from 14 to 40 weeks of gestation - Tongprasert F. (2014)
Objective: To develop reference ranges of fetal aortic and pulmonary valve diameter derived from volume datasets of spatio-temporal image correlation (STIC). Methods: A cross-sectional study was undertaken on low-risk pregnancies with well-established data from 14 to 40 weeks. Volume datasets of STIC were acquired for subsequent off-line analysis. Aortic and pulmonary valve diameters were measured in STIC multiplanar view using 4D-View version 9. Normal Z scores and centile reference ranges were constructed from these measurements against gestational age (GA) and biparietal diameter (BPD) as independent variables, using regression models for both mean and SD. Results: A total of 606 volume datasets were successfully measured. Normal reference ranges for predicting mean values and SD of aortic and pulmonary valve diameter were constructed based on best-fit equations (linear function) as follows: mean aortic diameter (mm) was modeled as a function of GA (weeks) and BPD (mm) as - 2.4838 + 0.2702× GA, (SD = 0.1482 + 0.0156× GA) and - 1.5952 + 0.0989× BPD (SD = 0.1672 + 0.00572× BPD). Mean pulmonary diameter was modeled as - 2.5924 + 0.2935× GA (SD = 0.2317 + 0.01524× GA) and - 1.6830 + 0.1083× BPD (SD = 0.1971 + 0.0059× BPD). Conclusion: We have provided nomograms and Z scores of fetal aortic and pulmonary valve diameters. These reference ranges may be a useful tool in the assessment of fetal cardiac abnormalities. © 2011 John Wiley & Sons, Ltd.